2021
DOI: 10.3390/v13010104
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Viruses and Inflammatory Bowel Disease

Abstract: Inflammatory bowel diseases (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is a multifactorial disease in which dietary, genetic, immunological, and microbial factors are at play. The role of enteric viruses in IBD remains only partially explored. To date, epidemiological studies have not fully described the role of enteric viruses in inflammatory flare-ups, especially that of human noroviruses and rotaviruses, which are the main causative agents of viral gastroenteritis. Genome-wide associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 96 publications
0
29
0
2
Order By: Relevance
“…Although NoV infections in AGE are mostly short and self-limited, chronic diarrhea in immunocompromised, malnourished, and elderly patients has been described [72][73][74]. On the other hand, immune-mediated disease may be triggered such as necrotizing enterocolitis in newborns [75,76] and inflammatory bowel disease exacerbations [77,78]. Dysregulation of enteric nervous and immune system may also be associated with the development of post-infectious irritable bowel syndrome [79,80].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Although NoV infections in AGE are mostly short and self-limited, chronic diarrhea in immunocompromised, malnourished, and elderly patients has been described [72][73][74]. On the other hand, immune-mediated disease may be triggered such as necrotizing enterocolitis in newborns [75,76] and inflammatory bowel disease exacerbations [77,78]. Dysregulation of enteric nervous and immune system may also be associated with the development of post-infectious irritable bowel syndrome [79,80].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…At least 37 G and 50 P genotypes of human and animal RVs have been distinguished (30). The most common combination of G and P genotypes of human RVs is G1P [8], G2P [4], G3P [8], G4P [8], and G9P [8], among which G1P [8] is the most prevalent worldwide (31). Caco-2 cells are similar to human intestinal epithelial cells in both structure and function, and are commonly used in in vitro experiments of RV infection (32).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelium is shed and destroyed, and the migration of RV from the crypts to the cilia is accelerated, resulting in a temporary loss of intestinal absorption capacity, and severe watery diarrhea occurs when RV is colonized in the intestine (2). Although its infection rate dropped after vaccination began, RV is still common worldwide and is considered to be one of the major pathogens causing intestinal inflammation in infants and many young children (3,4). Every year, over 200 million children younger than 5 years old are infected with RV, resulting in more than 200,000 deaths worldwide (5).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that IBD patients have altered microbiome and pro-inflammatory bacteria. When you treat a patient with Crohn disease and make an ostomy avoid intestinal transit in affected bowel segment it result in decreased inflammation [10][11][12][13].…”
Section: Pathogenesismentioning
confidence: 99%